2022
DOI: 10.3389/fnut.2022.843096
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lemon Essential Oil and Its Major Active Component, D-Limonene, on Intestinal Injury and Inflammation of E. coli-Challenged Mice

Abstract: Inflammatory diseases are a major threat to public health. Natural plant essential oils (EOs) possess anti-inflammatory and anti-oxidative activities. The objective of this study was to investigate the anti-inflammatory effect and mode of action of lemon essential oil (LEO), and its main active component, d-limonene, with different doses on intestinal inflammation of mice. Sixty-four 5-week-old male balb/c mice weighing 22.0 ± 1.5 g were randomly assigned into one of 8 treatments (n = 8/treatment), including n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Oregano oil supplementation upregulated the mRNA expression of intestinal barrier gene ZO-1 and Claudin-1 in the duodenum and Claudin-1 in the ileum of Eimeria -challenged broilers, which was consistent with the findings from Ruan et al (2021) . The upregulation of tight junction in the epithelial barrier was also reported in colorectal cancer mice model ( Leong et al, 2022 ), female pigs ( Hofmann et al, 2022 ), Escherichia coli -challenged mice ( Zhao et al, 2022 ), and colitis mice ( Raka et al, 2023 ). It is remarkable how essential oil interacts with the monolayer of enterocytes, probably due to their antioxidant capacity ( Toschi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 75%
“…Oregano oil supplementation upregulated the mRNA expression of intestinal barrier gene ZO-1 and Claudin-1 in the duodenum and Claudin-1 in the ileum of Eimeria -challenged broilers, which was consistent with the findings from Ruan et al (2021) . The upregulation of tight junction in the epithelial barrier was also reported in colorectal cancer mice model ( Leong et al, 2022 ), female pigs ( Hofmann et al, 2022 ), Escherichia coli -challenged mice ( Zhao et al, 2022 ), and colitis mice ( Raka et al, 2023 ). It is remarkable how essential oil interacts with the monolayer of enterocytes, probably due to their antioxidant capacity ( Toschi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 75%
“…Kummer et al [ 37 ] have reported that 500 mg/kg D-limonene reduced the TNF-α levels in the peritoneal exudate of mice. Zhao et al [ 20 ] have reported that 600 mg/kg LEO can alleviate the intestinal inflammation and injury induced by E. coli ATCC25922. However, in this study, 300 mg/kg LEO showed enhanced effects on the production of three inflammatory cytokines, which we speculate may be related to the active ingredient and the action dose of citrus EOs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, 300 mg/kg LEO showed enhanced effects on the production of three inflammatory cytokines, which we speculate may be related to the active ingredient and the action dose of citrus EOs. Some citrus EOs do not have anti-inflammatory effects at low concentrations [ 38 ], and Zhao et al reported that D-limonene, the main active component of LEO, also had a slight promoting effect in terms of E. coli -induced intestinal inflammation in mice at a dosage of 300 mg/kg [ 20 ]. Based on the above results, citrus EOs have an effect in alleviating intestinal inflammation caused by ETEC, which may derive from the dosage of LEO and the excellent anti-inflammatory effect of the chemical components, such as D-limonene and pinene in LEO [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations